Outcomes of Patients with Hematological Malignancies Admitted to the Intensive Care Unit at a Tertiary Care Center in Saudi Arabia - Ghazi Saud Alotaibi; Yazeed Alekrish; Fares Aldokhayel; Abdullah Alassaf; Musa Alzahrani; Mansour Aljabry; Bader Alshehri; Fatimah Alshalati; Sarah Sewaralthahab; Farjah Algahtani; Khalid Alsaleh; Ahmad Jamal; et al. (Saudi Journal of Medicine and Medical Sciences)
Background: Patients with hematological malignancies (HM) are at risk for complications, including neutropenia and admission to the intensive care unit (ICU). Granulocyte colony-stimulating factors (GCSF) can accelerate progenitor cells’ proliferation and differentiation, and thus compensate for neutropenia. In patients with HM admitted to ICUs in Saudi Arabia, the outcome and impact of GCSF use on neutropenia duration and severity is understudied. Objective: To evaluate the outcome and impact of GCSF on neutropenia in patients with HM admitted to the ICU of a tertiary care center in Saudi Arabia. Methods: This retrospective study included all consecutive patients diagnosed with an HM admitted to the ICU at King Saud University Medical City, Riyadh, Saudi Arabia, from 2018 to 2022. Data on demographics, clinical information, ICU admission, and outcomes were collected. Results: A total of 44 patients with HM admitted to the ICU were included, of which 43.2% were females and the mean age was 50.2 ± 21.1 years. The mean length of ICU stay was 12.3 ± 14.7 (range: 0–62) days. ICU mortality was 61.4%, with no further mortality within 90 days after discharge. There was no significant association between survival and age (P = 0.205), gender (P = 0.7), and neutropenia (P = 0.566) or the use of GCSF prior to ICU admission (P = 0.882). There was a significant association between the category of ICU intervention and survival (P = 0.007). Conclusion: Patients with hematological malignancies who were admitted to an ICU in Saudi Arabia had a high mortality, regardless of neutropenia or the use of granulocyte colony-stimulating factor.